Molecular cloning and expression study of proline-rich ena/vasp ligand 2b (PREL-2b) gene in zebrafish development - Su, Sin Ling (Universiti Malaysia Sarawak (UNIMAS), 2011)
Proline rich Ena/VASP Ligand 2 (PREL-2) is known as Lamellipodin (Lpd) and Rasassociated and pleckstrin homology domains-containing protein 1 (RAPH1). Proline rich Ena/VASP Ligand 2 (PREL-2) is constituted from Ras-Association (RA), Pleckstrin Homology (PH) domain and a long proline stretch at C-terminal. PREL-2 was found to have significant functions on cell signaling and direct migration, promoting axon guidance, affecting focal adhesion and regulating lamellipodial dynamics. PREL-2 gene in zebrafish is duplicated into PREL-2a and PREL-2b due to genome duplication. To establish the expression pattern of PREL-2b gene in developing zebrafish, total RNA was isolated from 10 embryonic stages of developing zebrafish. Reverse Transcriptase-PCR revealed that PREL-2b gene was expressed along the embryonic development, started from 3hpf and remained until 5dpf. Amplified cDNA sequences were confirmed by nucleotide sequencing, given an output result of 652bp. The gene was later cloned. The findings provide an insight that PREL-2b gene plays an important role during zebrafish embryonic development.